The East is Red… again! How Central and Eastern European Perceptions of China are influenced by the Specters of Communism and Russia - Dr. Peter Collin; Dr. Ford Turcsányi (Al-Qanṭara, 2022)
Abstract China has rapidly risen to prominence in Central and Eastern Europe over the past ten years (CEE). Will it split Europe apart? Could these formerly communist nations re-align with the East's communist superpower? Or does their prior exposure to communism and Russia make them suspicious of China? This article investigates what the results of a fall 2020 poll conducted in six CEE nations—the Czech Republic, Hungary, Latvia, Poland, Serbia, and Slovakia—can reveal about the factors influencing CEE attitudes toward China. It implies that China has emerged as a "second Eastern power" after Russia, which many CEE nations have come to identify with. Although there are significant differences between CEE publics' perceptions of China, perceptions of both Russia and China are consistently influenced by people's East or West self-identifications and attitudes toward both the past and present of communism. For all of the CEE, but especially for Latvia and Poland, where opinions toward their enormous Russian neighbour appear to almost entirely filter perceptions of China, Russia looms huge. We end by considering the effects of these conclusions regarding the composition of CEE public opinion toward China on the future of the "17+1" mechanism and CEE-China relations in general.